Organization and administration of adult education programs : a guide for practitioners - Schmidt, Steven W.; Yelich Biniecki, Susan M. (Adult education special topics: theory, research and practice in lifelong learning, 2023)
"Administrators of adult education programs work in dynamic and ever-changing environments. They are continually challenged with a myriad of issues related to programming, budgeting, marketing, strategic planning, funding, human resource management, and other topics. With decades of real-world experience in the field, Steven Schmidt and Susan Yelich Biniecki have developed a second edition of their practical guide for those who are involved in the organization and administration of educational programs for adults. Whether you work in the human resource department of a corporation, a grass-roots community organization, a higher education unit, a consulting company, or any other type of organization that provides adult education, this book is for you. In a no-nonsense approach, Organization and Administration of Adult Education Programs: A Guide for Practitioners "talks" to you as an administrator about topics that are important to you. Guidelines, processes, and procedures discussed in the book can help to make you a more effective practitioner. Scenarios, role plays, and activities are also included for classroom use and personal reflection"--Resumé vydavatel